2020
DOI: 10.1103/physreva.102.033306
|View full text |Cite
|
Sign up to set email alerts
|

Unified model of ultracold molecular collisions

Abstract: A scattering model is developed for ultracold molecular collisions, which allows inelastic processes, chemical reactions, and complex formation to be treated in a unified way. All these scattering processes and various combinations of them are possible in ultracold molecular gases, and as such this model will allow the rigorous parametrization of experimental results. In addition we show how, once extracted, these parameters can to be related to the physical properties of the system, shedding light on fundamen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 82 publications
7
30
0
Order By: Relevance
“…We see no evidence for collisional energy shifts, which would be observed by a change in the energies of the states when the density reduces over the course of each Ramsey measurement (see Supplementary Information). This is consistent with previous observations [25], and the absence of collisional energy shifts or decoherence may be expected as short-range collisions in the gas lead to loss of molecules with high probability [35][36][37][38]. Measurements of the coherence out to longer times will require confinement of the molecules to a 3D optical lattice [39] , optical tweezers [40][41][42], or the use of alternative trapping techniques such as a blue-detuned optical trap [43] to avoid losses from the optical excitation of two-molecule collision complexes [36,44].…”
supporting
confidence: 93%
“…We see no evidence for collisional energy shifts, which would be observed by a change in the energies of the states when the density reduces over the course of each Ramsey measurement (see Supplementary Information). This is consistent with previous observations [25], and the absence of collisional energy shifts or decoherence may be expected as short-range collisions in the gas lead to loss of molecules with high probability [35][36][37][38]. Measurements of the coherence out to longer times will require confinement of the molecules to a 3D optical lattice [39] , optical tweezers [40][41][42], or the use of alternative trapping techniques such as a blue-detuned optical trap [43] to avoid losses from the optical excitation of two-molecule collision complexes [36,44].…”
supporting
confidence: 93%
“…Christianen et al [83] recently considered a lossy QDT model of such resonances. They concluded that if the complexes are lost rapidly once formed and Γs inc = d/2π, such that T s inc = 1 in equation ( 3), the loss rate is represented by y = 0.25, as opposed to the y = 1 implicit in the model of Croft et al [82]. The reasons for this apparent disagreement are not clear at present, but both methods rely on averaging over a large number of resonances.…”
Section: Resonance Widths and Lifetimes Of Collision Complexesmentioning
confidence: 99%
“…All of the physics investigated above strongly depends on the capacity to fine-tune the dipolar length a dd and the two-body s-wave scattering length a s of an ultracold molecular gas. In addition, in contrast to atoms, ground-state molecules can also lead to two-body collisional losses, no matter if the molecules are chemically reactive or not [90,91]. As a result, the scattering length associated with molecular collisions becomes a complex quantity, with an imaginary part directly linked to the magnitude of the molecular losses [92].…”
Section: Controlling the Scattering Properties Of A Molecular Gasmentioning
confidence: 99%